1994
DOI: 10.1073/pnas.91.18.8502
|View full text |Cite
|
Sign up to set email alerts
|

Transcript cleavage by RNA polymerase II arrested by a cyclobutane pyrimidine dimer in the DNA template.

Abstract: A current model for transcription-coupled DNA repair is that RNA polymerase, arrested at a DNA lesion, directs the repair machinery to the transcribed strand of an active gene. To help elucidate this role of RNA polymerase, we constructed DNA templates containing the major late promoter of adenovirus and a cyclobutane pyrimidine dimer (CPD) at a specific site. CPDs, the predominant DNA lesions formed by ultraviolet radiation, are good substrates for transcriptioncoupled repair. A CPD located on the transcribed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
236
2
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(255 citation statements)
references
References 39 publications
13
236
2
2
Order By: Relevance
“…At doses of UVB which impaired the induction of p21 Waf1/Cip1 protein expression (approximately 500 J/m 2 and over), apoptosis was induced. It has been shown that UV radiation transciently inhibits both DNA and RNA synthesis in vivo (Mayne and Lehmann, 1982) and completely blocks RNA pol II transcription in vitro (Donahue et al, 1994;Selby et al, 1997). Furthermore, it has been suggested previously that blockage of RNA polymerase may trigger UV-induced apoptosis (Ljungman and Zhang, 1996).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At doses of UVB which impaired the induction of p21 Waf1/Cip1 protein expression (approximately 500 J/m 2 and over), apoptosis was induced. It has been shown that UV radiation transciently inhibits both DNA and RNA synthesis in vivo (Mayne and Lehmann, 1982) and completely blocks RNA pol II transcription in vitro (Donahue et al, 1994;Selby et al, 1997). Furthermore, it has been suggested previously that blockage of RNA polymerase may trigger UV-induced apoptosis (Ljungman and Zhang, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…For example, 6 and 12 h incubations with mimosine elevate p21 Waf1/Cip1 levels but the levels decline after UV-irradiation ( Figure 9); however, a 24 h incubation with mimosine results in the maintenance of high levels of p21 Waf1/Cip1 following irradiation. These post-irradiation di erences in p21 Waf1/Cip1 levels must re¯ect di erences in the relative rates of translation and proteolysis since transcription is blocked at the dose of UVB used (2000 J/m 2 ) (Mayne and Lehmann, 1982;Donahue et al, 1994;Selby et al, 1997). Both p21 Waf1/Cip1 and p53 protein degradation proceed via ubiquitination (Maki et al, 1996;Maki and Howley, 1997) and p53 stabilization involves reduced ubiquitination (Maki and Howley, 1997).…”
Section: P21-dependent Cell Cycle Arrest In Late G 1 Protects A431 Cementioning
confidence: 99%
“…Effect of CSB on RNAPII Stalled by DNA Damage. Elongation by RNAPII is known to be completely blocked by a TϽϾT in the template strand (24). To examine a possible role of CSB on the blocked polymerase we constructed pPU192, which possesses a TϽϾT located in the template strand at positions 149-150 downstream from the adenovirus major late promoter transcription start site (14).…”
Section: Biochemistry: Selby and Sancarmentioning
confidence: 99%
“…One possibility is that the transcription machinery reads or skips over regions containing thymine dimers in the DNA. We consider this very unlikely because it has been demonstrated that a cyclobutane pyrimidine dimer located on the template strand, but not on the nontranscribed strand, blocks transcriptional elongation and arrests the RNA polymerase at the site of the lesion (Protic-Sabljic and Kraemer, 1985;Sauerbier and Hercules, 1978;Selby and Sancer, 1990;Donahue et al, 1994). At best, this would result in the production of truncated and therefore inactive CAT enzyme.…”
Section: Discussionmentioning
confidence: 99%